DESIGN OF AUTOMATIC COOKING MACHINE EQUIPPED WITH TEMPERATURE, TIMER, SPEED CONTROL - Susi Tri Umaroh; Muhammad Ichsan Khofi; Khoirul Huda; Ahmad Setyo Purnomo; Amalia Forma Alfianti; Agung Prijo Budijono (Journal of International Conference Proceedings (JICP), 2018)
The purpose The purpose of this study is to provide solutions to existing problems in SME Fried Onion in Sidoarjo Region on the process of frying still conventional and often experience gap. Methodology The method used is to utilize technology TTS (Temperature, Timer, Speed Control) on the onion parser to produce fried onions with good quality and stable cooking temperature. Result, The expected result is to improve the quality of fried onion frying result which will affect the productivity of SME BawangGoreng can increase up to 2 times which initially only able to fry onion as much as 2 kg, can become 4 kg in one process of frying. The findings, The findings of this study are the use of Temperature, Timer, and Speed Control (TTS) technology to overcome the problems of conventional frying process and onion garlic during frying process. Keywords: frying machine, fried onion, thermocontrol, timer, speed regulator